Pengaruh Motivasi, Kompensasi dan Lingkungan Kerja terhadap Kinerja Karyawan PT. Asia Hoda Indonesia - Halipi Hazizan; Sri Wahyuningsih (Journal on Education, 2023)
The purpose of the research to be achieved is to determine to what extent the influence of motivation, compensation, and work environment on the performance of PT employees. Asia Hoda Indonesia. To test and prove research hypotheses using spss application version 26. Work motivation has a positive and significant effect on employee performance. Compensation has a positive and significant effect on employee performance. The work environment has a positive and significant effect on employee performance. And motivation, compensation and work environment have a positive and significant influence on employee performance. This is shown by the calculated F value of 103.850 > the table of 3.183, and the signification value of 0.000 < 0.05. This shows that motivation, compensation, and work environment together have a positive and significant influence on employee performance.